Biomechanical comparison of different graft positions for single-bundle anterior cruciate ligament reconstruction - Kato, Yuki (Springer-Verlag, 2012)
PURPOSE: Recent reports have highlighted the importance of an anatomic tunnel placement for anterior cruciate ligament (ACL) reconstruction. The purpose of this study was to compare the effect of different tunnel positions for single-bundle ACL reconstruction on knee biomechanics. METHODS: Sixteen fresh-frozen cadaver knees were used. In one group (n = 8), the following techniques were used for knee surgery: (1) anteromedial (AM) bundle reconstruction (AM–AM), (2) posterolateral (PL) bundle reconstruction (PL–PL) and (3) conventional vertical single-bundle reconstruction (PL-high AM). In the other group (n = 8), anatomic mid-position single-bundle reconstruction (MID–MID) was performed. A robotic/universal force-moment sensor system was used to test the knees. An anterior load of 89 N was applied for anterior tibial translation (ATT) at 0°, 15°, 30° and 60° of knee flexion. Subsequently, a combined rotatory load (5 Nm internal rotation and 7 Nm valgus moment) was applied at 0°, 15°, 30° and 45° of knee flexion. The ATT and in situ forces during the application of the external loads were measured. RESULTS: Compared with the intact ACL, all reconstructed knees had a higher ATT under anterior load at all flexion angles and a lower in situ force during the anterior load at 60° of knee flexion. In the case of combined rotatory loading, the highest ATT was achieved with PL-high AM; the in situ force was most closely restored with MIDMID, and the in situ force was the highest AM–AM at each knee flexion angle. CONCLUSION: Among the techniques, AM–AM afforded the highest in situ force and the least ATT.